PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PEMBUATAN KASAB GUNA MENINGKATKAN PENDAPATAN DAN MENCIPTAKAN LAPANGAN USAHA DI KECAMATAN BENDAHARA KABUPATEN ACEH TAMIANG - Meri Andriani; Rita Syntia (Global Science Society, 2020)
Bendahara Sub District is currently promoting human empowerment, as instructed by the Government of Aceh Tamiang. Human empowerment, especially for women, began this year by the Chairperson of Family Welfare Development (PKK). The service team conducted a survey in Bendahara Sub District, where it was found that many people did not have work, even found that many teenagers who had finished college did not have a job, this was also recognized by Datok Penghulu. The method used was through the Kasab training for women, who then opened a business for Kasab products that had been obtained. The target to be achieved is to increase the economic income of the residents of Bendahara Sub District, starting from the improvement of the economic opinion of the women who have been trained and the transfer of technology and knowledge between lecturer and partners so as to create empathy and sympathy between partners and lecturers. Targets can be accomplished by training and mentoring in managing Kasab product business